1999
DOI: 10.1046/j.1460-9568.1999.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar granule‐cell‐specific GABAA receptors attenuate benzodiazepine‐induced ataxia: evidence from α6‐subunit‐deficient mice

Abstract: Benzodiazepine- and alcohol-induced ataxias in rodents have been proposed to be affected by the gamma-aminobutyric acid type A (GABAA) receptor alpha 6 subunit, which contributes to receptors specifically expressed in cerebellar granule cells. We have studied an alpha 6 -/- mouse line for motor performance and drug sensitivity. These mice, as a result of a specific genetic lesion, carry a precise impairment at their Golgi-granule cell synapses. On motor performance tests (rotarod, horizontal wire, pole descend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…High doses of ethanol (2 g kg −1 ) have been reported to similarly impair wild-type and Gabra6 −/− mice in rotarod tests 40 , and at ethanol doses of 3.5 g kg −1 , no significant differences have been observed between wild type and Gabra6 −/− in a LORR test 41,42 . At such high ethanol doses, we also find no change for Gabra6 100R/100R and Gabra6 100Q/100Q rats in rotarod performance (data not shown) or in LORR (Fig 5e,f).…”
Section: Gabra6 100q Allele and Behavioral Sensitivity To Ethanolmentioning
confidence: 94%
“…High doses of ethanol (2 g kg −1 ) have been reported to similarly impair wild-type and Gabra6 −/− mice in rotarod tests 40 , and at ethanol doses of 3.5 g kg −1 , no significant differences have been observed between wild type and Gabra6 −/− in a LORR test 41,42 . At such high ethanol doses, we also find no change for Gabra6 100R/100R and Gabra6 100Q/100Q rats in rotarod performance (data not shown) or in LORR (Fig 5e,f).…”
Section: Gabra6 100q Allele and Behavioral Sensitivity To Ethanolmentioning
confidence: 94%
“…No compensation by the a1 subunit was detected in glomeruli or in the molecular layer of a6 0/0 mice (73), indicating that the a1 and a6 subunit are regulated independently, although their genes are present in the same chromosomal cluster (75). Interestingly, while a6 0/0 mice display no major spontaneous phenotype, a clear motor deficit could be shown upon treatment with diazepam, which could be reversed by flumazenil, indicating that it was mediated by the remaining, mainly postsynaptic, GABA A receptors in these mice (76).…”
Section: Effects Of Targeted Subunit Gene Deletion On Cerebellar Gabamentioning
confidence: 99%
“…Functionally, a loss of modulation of sIPSCs by the neurosteroid THDOC selectively occurs in granule cells, but not stellate cells of d 0/0 mice (78), underscoring the importance of d-GABA A receptors for the in vivo action of neurosteroids (79). Behaviorally, deletion of the d subunit gene produces no overt impairment in motor function or motor learning, similarly to the a6 subunit gene (76). This observation should not lead to the conclusion that tonic inhibition mediated by extrasynaptic GABA A receptors in granule cells is irrelevant.…”
Section: Effects Of Targeted Subunit Gene Deletion On Cerebellar Gabamentioning
confidence: 99%
“…One of the most commonly used tests of motor incoordination is the rotarod (1)(2)(3)(4), which has two variants: the accelerating rotarod (ARR) and the fixed-speed rotarod (FSRR). Studies of inbred strains (5)(6)(7)(8), selected lines (9), and transgenic animals (10)(11)(12) have shown that rotarod performance is highly influenced by genetic background in mice. Genetically distinct mice often differ in their undrugged ability to perform, and differ in their sensitivities to ethanol and other drugs on the task.…”
mentioning
confidence: 99%